Cognitive function in soccer athletes determined by sleep disruption and self-reported health, yet not by decision-reinvestment - Pourhassan, Jasmin; Sarginson, Jane; Hitzl, Wolfgang; Richter, Kneginja (Frontiers in Neurology, 2023)
Background Sleep disruption (SD) increases sympathetic activity and cortisol secretion, and delays cognitive functions such as reaction-time (RT). Sympathetic activity of disturbed sleepers, is similar to those of so-called decision-reinvesters. Decision-reinvestment refers to traits in individuals with greater tendency to ruminate and reinvest in their decisions, with significant decrease in both motor-control and cognitive performance. Decision-making quality is a crucial attribute to athletic performance which relies on RT. Consequently, SD affects pitch-performance negatively, particularly in decision-reinvesters. This observational pilot-study examined the relationship between SD and cognitive function, perceived health, as well as reinvestment strategies. The hypothesis was that athletes with lower SD perceive their health better, report lower stress levels, perform better in cognitive tasks, and show lower tendency for decision-reinvestment. Methods Twenty-one football player recorded their sleep with fit-trackers for 7 nights. Participants self-reported their mental and physical health, decision-reinvestment strategy, sleep behaviour, and perceived stress levels. Athletes then performed a set of cognitive tests to examine memory function (Backwards Corsi), selective attention (STROOP), and cognitive flexibility (Wisconsin Card Sorting Test, WCST). Normality was tested with a Shapiro-Wilk test, and analysed with a Pearson's or Spearman's correlation test. Results Significant correlation appeared between extended sleep-interruptions and Backwards Corsi RT, r = 0.66, p = 0.010, as further in total sleep time and wellbeing r = 0.50, p = 0.029. A negative correlation exist in regard of pain scores and Backwards Corsi scores r = −0.57, p = 0.110. Physical health correlated with error-rates in the WCST, r = 0.69, p ≤ 0.001. Also, reinvestment negatively correlated with physical health, r = −0.80, p ≤ 0.001. Conclusion Wellbeing relies on total sleep-time. Athletes with extended sleep-interruptions are slower in recalling memory, and those with greater reported pain have lower memory scores. Participants who rate physical health greater, have more error-rates in the WCST; indicating that cognitive flexibility is enhanced in individuals with inferior perceived health. However, individuals with lower physical health scores also have greater tendency to ruminate and reinvest in decisions, suggesting interrelation between reinvestment and physical health.